The history and politics of the Bedouin reimagining nomadism in modern Palestine - Assi, Seraj (Routledge studies on the Arab-Israeli conflict, 2020)
This book examines contending visions on nomadism in modern Palestine, with a special focus on the British Mandate period. Extending from the late Ottoman period to the founding of the State of Israel, it highlights both ruptures and continuities with the Ottoman past and the Israeli present, to prove that nomadism was not invented by the British or the Zionists, but is the shared legacy of Ottoman, British, Zionist, Palestinian, and most recently, Israeli attitudes to the Bedouin of Palestine. Drawing on primary sources in Arabic and Hebrew, the book shows how native conceptions of nomadism have been reconstructed by colonial and national elites into new legal taxonomies rooted in modern European theories and praxis. By undertaking a comparative approach, it maintains that the introduction of these taxonomies transformed not only native Palestinian perceptions of nomadism, but perceptions that characterized early Zionist literature. The book breaks away from the Arab/Jewish duality by offering a comparative and relational study of the main forces operating under the Mandate: British colonialism, Labor Zionism, and Arab nationalism. Special attention is paid to the British side, which covers the first three chapters. Each chapter represents a formative stage of British colonial enterprise in Palestine, extending from the late Ottoman down to the postwar and the Mandate periods. A major theme is the nexus of race and ethnography reshaping British perceptions of the Bedouin of Palestine before and during the early phases of the Mandate, and the ways these perceptions guided the administrative division of the country along newly demarcated racial boundaries